Prevalence of Soil-Transmitted Helminthiasis and Its Association with Pediatric Diarrhea in Perobatang Village, Southwest Sumba - Sungkar, Saleha; Soleman, Imam Rahadian (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Diarrhea is a prevalent health issues in developing countries and often linked to soil-transmitted helminthiasis (STH). This study aims to investigate the association between STH and diarrhea in Perobatang, Southwest Sumba. Method: A cross-sectional study was conducted in Perobatang, January 2017. Participants were children aged 1–15 years. Stool samples were collected from each child and examined macroscopically for signs of diarrhea and microscopically for STH eggs. Positive cases were treated with albendazole 400 mg. Result: A total of 333 samples were analyzed and 257 children were infected with STH (77%). The prevalence of A. lumbricoides was 56%, T. trichiura was 55%, and hookworm was 5%. Mixed infections were more common in children 6–15 years. 92 children (28%) had diarrhea. There is an association between the STH infection (combination of all three worm species) and diarrhea incidence (chi-square test, p=0.041). However, there is no association between the prevalence of single infections or the combination of two worm species and diarrhea incidence. Conclusion: STH infections are associated with incidence of diarrhea in Perobatang, Sumba Barat Daya. This finding highlights the necessity for targeted, community- based interventions by local stakeholders to effectively address and mitigate this public health challenge.